2005
DOI: 10.1364/ol.30.000132
|View full text |Cite
|
Sign up to set email alerts
|

Experimental observation of orthogonally polarized time-delayed optical soliton trapping in birefringent fibers

Abstract: Propagation of two orthogonally polarized time-delayed optical solitons in low-birefringence optical fiber is studied experimentally. We demonstrate soliton trapping and collisions and also the ability to control the separation and shape of soliton pulses by varying the power at the input of the fiber.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
20
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 8 publications
0
20
0
Order By: Relevance
“…In addition to affecting these nonlinear processes, polarization trapping can be used to affect the polarization mode delay [4]. Here it was shown that it is possible to control the separation and shape of two polarized solitons by varying the amount of input power.…”
Section: Fiber Considerationsmentioning
confidence: 99%
“…In addition to affecting these nonlinear processes, polarization trapping can be used to affect the polarization mode delay [4]. Here it was shown that it is possible to control the separation and shape of two polarized solitons by varying the amount of input power.…”
Section: Fiber Considerationsmentioning
confidence: 99%
“…8 c, which means that the two polarization components of the vector optical soliton propagate with nearly matched, ultraslow propagating velocities. As we have stressed, different from the passive media such as optical fibers [2,3,4,5,6,7,8,9,10] the parameters of our present EIT medium can be actively manipulated. Consequently the coefficients of Eq.…”
mentioning
confidence: 99%
“…In recent years, considerable attention has been paid to the temporal [1,2,3,4,5,6] and spatial [7,8,9, 10] vector optical solitons in various nonlinear systems. Due to their remarkable property, vector optical solitons have promising applications for the design of new types of all-optical switches and logic gates [12].Up to now, most vector optical solitons are produced in passive media such as optical fibers [2,3,4,5,6,7,8,9,10], in which far-off resonance excitation schemes are employed in order to avoid unmanageable optical attenuation and distortion. However, due to the lack of distinctive energy levels, the nonlinear effect in such passive media is very weak, and hence to form vector solitons a very high input light-power is required.…”
mentioning
confidence: 99%
See 2 more Smart Citations